Pengaruh Media Sosial Dan Manajemen Risiko Terhadap Keputusan Investasi Berdasarkan Perilaku Investor Sebagai Variabel Intervening: (Studi Kasus Pada Mahasiswa Selaku Investor dan Pengurus Galeri Investasi Bursa Efek Indonesia di Universitas Kota Bengkulu) - Dinda Rahma Aprilia; Sintia Safrianti; Janusi Waliamin (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to determine the influence of social media and risk management on investment decisions based on investor behavior as an intervening variable. The approach used in this study is quantitative, with data collection techniques involving questionnaires obtained directly from the original source (respondents). The population of this study consists of all students as investors and managers of the Indonesia Stock Exchange Investment Gallery (GIBEI) at Bengkulu City University, totaling 115 individuals. The sample was selected using total sampling, where all investors and GIBEI managers were included as the sample. The research data was analyzed using the SmartPLS version 4 analysis tool. The results of the study indicate that the direct effect of the first hypothesis, social media, has a positive and significant effect on investment decisions; the second hypothesis, risk management, has a positive and significant effect on investment decisions; the third hypothesis, social media, has a positive and significant effect on investor behavior; the fourth hypothesis, risk management, has a significant effect on investor behavior; and the fifth hypothesis, investor behavior, has a positive and significant effect on investment decisions. The results of the indirect effect analysis indicate that the sixth hypothesis, social media, has a significant effect on investment decisions through investor behavior, and the seventh hypothesis, risk management, has a significant effect on investment decisions through investor behavior. Overall, the results of this study indicate that social media and risk management have a significant effect on investment decisions based on investor behavior as an intervening variable.